Dual Regulation of the Small RNA MicC and the Quiescent Porin OmpN in Response to Antibiotic Stress in Escherichia coli - Dam, Sushovan (Antibiotics (Basel), 2017)
Antibiotic resistant Gram-negative bacteria are a serious threat for public health. The permeation of antibiotics through their outer membrane is largely dependent on porin, changes in which cause reduced drug uptake and efficacy. Escherichia coli produces two major porins, OmpF and OmpC. MicF and MicC are small non-coding RNAs (sRNAs) that modulate the expression of OmpF and OmpC, respectively. In this work, we investigated factors that lead to increased production of MicC. micC promoter region was fused to lacZ, and the reporter plasmid was transformed into E. coli MC4100 and derivative mutants. The response of micC–lacZ to antimicrobials was measured during growth over a 6 h time period. The data showed that the expression of micC was increased in the presence of β-lactam antibiotics and in an rpoE depleted mutant. Interestingly, the same conditions enhanced the activity of an ompN–lacZ fusion, suggesting a dual transcriptional regulation of micC and the quiescent adjacent ompN. Increased levels of OmpN in the presence of sub-inhibitory concentrations of chemicals could not be confirmed by Western blot analysis, except when analyzed in the absence of the sigma factor σ(E). We suggest that the MicC sRNA acts together with the σ(E) envelope stress response pathway to control the OmpC/N levels in response to β-lactam antibiotics.